Advances in safety of lithium-ion batteries for energy storage: Hazard characteristics and active suppression techniques - Yan Wang; Tianmin Yu; Jie Chen; Baobin Gao; Mingqiao Yu; Jiateng Zhu (Energy Reviews)
Lithium-ion batteries (LIBs) are widely regarded as established energy storage devices owing to their high energy density, extended cycling life, and rapid charging capabilities. Nevertheless, the stark contrast between the frequent incidence of safety incidents in battery energy storage systems (BESS) and the substantial demand within the energy storage market has become increasingly prominent. Firstly, despite the escalating demand for energy density in BESS, in-depth understanding of thermal runaway (TR) in large-capacity LIBs and the associated risks posed by battery venting gases (BVG) remains elusive. Secondly, the absence of consensus regarding the selection of fire extinguishing agents and the development of fire suppression strategies for BESS has resulted in prevailing technological inadequacies in active suppression measures. This manuscript comprehensively reviews the characteristics and associated influencing factors of the four hazard stages of TR, TR propagation, BVG accumulation, and fire (BVG combustion and explosion), particularly focusing on the spatial characteristics of energy storage. Combining the above analysis, the suppression mechanisms, effects, and applicable hazard stages of extinguishing agents are analyzed, and the positive effects of fire suppression strategies are discussed. Additionally, the experimental research, mathematical calculation and numerical simulation methods pertaining to the combustion and explosion characteristics are summarized, alongside offering corresponding research suggestions and prospects aimed at fostering advancements in BESS safety.